2016
DOI: 10.3390/g7020013
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Framing, Inequity and History in a Corruption Game: Some Experimental Evidence

Abstract: Abstract:We investigate the role of framing, inequity in initial endowments and history in shaping behavior in a corrupt transaction by extending the one-shot bribery game introduced by to a repeated game setting. We find that the use of loaded language significantly reduces the incidence of bribery and increases the level of punishment. Punishment of bribery leads to reduced bribery in future. The evidence suggests that this game captures essential features of a corrupt transaction, over and above any sentim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 47 publications
1
13
0
3
Order By: Relevance
“…For instance, research has shown that corruption increases when individuals interact repeatedly with the same partner (Abbink, 2004), that the route to corruption leads over a steep cliff rather than down a slippery slope (Köbis et al, 2017), and that descriptive norms affect corruption (Köbis et al, 2015). Moreover, studies have shown that individuals are willing to punish corrupt behavior (Cameron et al, 2009;Chaudhuri et al, 2016). However, no systematic research has yet investigated the role of individuals who allow the corruption to result in a beneficial outcome for the corrupt individual by covering up the initial transgression (but see Gino & Bazerman, 2009).…”
mentioning
confidence: 99%
“…For instance, research has shown that corruption increases when individuals interact repeatedly with the same partner (Abbink, 2004), that the route to corruption leads over a steep cliff rather than down a slippery slope (Köbis et al, 2017), and that descriptive norms affect corruption (Köbis et al, 2015). Moreover, studies have shown that individuals are willing to punish corrupt behavior (Cameron et al, 2009;Chaudhuri et al, 2016). However, no systematic research has yet investigated the role of individuals who allow the corruption to result in a beneficial outcome for the corrupt individual by covering up the initial transgression (but see Gino & Bazerman, 2009).…”
mentioning
confidence: 99%
“…For example, Abbink and Hennig-Schmidt (2006) introduced first and second movers' roles as "firm" and "public official," respectively, and changed the labels associated with decision options to "private payment" and "grant permission." A similar framing strategy has been followed in a number of other papers (Abbink et al, 2014;Barr and Serra, 2009;Chaudhuri et al, 2016), even using a very direct word such as "bribe" in some (Alatas et al, 2009;Banerjee, 2016;Cameron et al, 2009).…”
Section: Experimental Studies Of Bribery and Relevant Social Normsmentioning
confidence: 99%
“…Desde el punto de vista experimental, se ha recurrido a variaciones del marco para resaltar las connotaciones morales y normativas de una situación de coimas (Abbink y Hennig-Schmidt, 2006;Banerjee, 2016;Barr y Serra, 2009;Chaudhuri, Paichayontvijit, y Sbai, 2016). Las variaciones del marco comúnmente han involucrado cambios en los nombres asociados a los roles de los participantes (por ejemplo, "participante A" y "participante B" en la versión abstracta o neutra, versus "empresa" o "ciudadano" y "funcionario público" en la versión semánticamente cargada) y las palabras utilizadas para designar algunas de las acciones disponibles ("transferencia" versus "pago privado" o "coima" en los marcos neutro y cargado, respectivamente).…”
Section: Introductionunclassified
“…Las variaciones del marco comúnmente han involucrado cambios en los nombres asociados a los roles de los participantes (por ejemplo, "participante A" y "participante B" en la versión abstracta o neutra, versus "empresa" o "ciudadano" y "funcionario público" en la versión semánticamente cargada) y las palabras utilizadas para designar algunas de las acciones disponibles ("transferencia" versus "pago privado" o "coima" en los marcos neutro y cargado, respectivamente). No obstante, la comparación de estas variaciones del marco ha arrojado resultados mixtos: ausencia de efecto de marco (Abbink y Hennig-Schmidt, 2006;Cameron et al, 2009), presencia de efecto de marco (Banerjee, 2016;Chaudhuri, Paichayontvijit y Sbai, 2016); Barr y Serra (2009) presentan resultados mixtos dependientes del nivel de externalidad negativa involucrada.…”
Section: Introductionunclassified